Community Service Order in Indonesia: Between Alternatives and Transformation in the Reconstruction of the Penal System - Didik Purnomo; Anis Widyawati; Bhanu Prakash Nunna; Rasdi Rasdi; Muhammad Azil Maskur (Universitas Negeri Semarang, 2026)
The integration of community service orders into the national criminal justice system indicates a shift away from a punitive approach dominated by incarceration toward the use of non-custodial sanctions more oriented toward rehabilitation and social reintegration. Nevertheless, studies systematically linking normative constructions, institutional readiness, and the community's role in their implementation remain relatively limited. This study aims to analyze the normative construction and institutional readiness for the application of community service as a substitute for short-term imprisonment, and to assess its consistency with criminal justice reform in Indonesia. This study uses a normative juridical method with a legislative and comparative approach, through an analysis of national legal regulations and practices in several countries that have institutionalized community service orders. The results of the study show that although the normative framework is relatively comprehensive, its implementation effectiveness is greatly influenced by the consistency of judges' decisions, the readiness of the supervision and guidance system, and the level of collaboration between law enforcement officers and the community. The main challenge lies in the limitations of probation infrastructure and the tendency of a still prison-oriented penal culture. This study offers an innovation in the form of an integrative framework that links normative design, institutional capacity, and social participation as prerequisites for effective implementation. Thus, community service orders can be understood not only as an alternative to imprisonment but also as a policy instrument that can support the development of a penal system that is more proportional, rehabilitative, and oriented towards social reintegration.